1994
DOI: 10.2134/jeq1994.00472425002300050012x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Decomposition and Denitrification during Plant Decomposition in an Organic Soil

Abstract: Nitrate concentrations in groundwater have been shown to be reduced during passage through riparian soils and a possible mechanism for this reduction is bacterial denitrifieation. For denitrification to occur there must be sufficient available C as an energy source. We examined the competition for organic substrate between microbial processes during the anaerobic decomposition of plant matter in a laboratory study. Fresh and senescent pine needles (Pinus radiata D. Don) and watercress leaves (Rorippa nasturtiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 0 publications
3
21
1
Order By: Relevance
“…Carbon inputs from freshwater plants, including P. virginica and P. cordata, decompose more quickly than brackish or saline species, including S. alterniflora, because they have a higher N content (i.e., a lower C:N ratio) and a lower cellulose and lignin content (Odum and Heywood, 1978). The observation that microbial activity on soil carbon mass basis was higher for the soils with higher quality carbon is consistent with a number of previous reports (Groffman et al, 1991;Schipper et al, 1994;Hill and Cardaci, 2004). Several peatland studies also have demonstrated that both CO 2 and CH 4 production are related to the lability of soil organic carbon compounds Bridgham and Richardson, 1992;Crozier et al, 1995), suggesting that carbon quality has a strong influence on rates of greenhouse gas production (Bridgham and Richardson, 1992;Wagner et al, 2005;Reiche et al, 2010).…”
Section: Role Of Electron Donors: Carbon Quantity and Qualitysupporting
confidence: 90%
See 1 more Smart Citation
“…Carbon inputs from freshwater plants, including P. virginica and P. cordata, decompose more quickly than brackish or saline species, including S. alterniflora, because they have a higher N content (i.e., a lower C:N ratio) and a lower cellulose and lignin content (Odum and Heywood, 1978). The observation that microbial activity on soil carbon mass basis was higher for the soils with higher quality carbon is consistent with a number of previous reports (Groffman et al, 1991;Schipper et al, 1994;Hill and Cardaci, 2004). Several peatland studies also have demonstrated that both CO 2 and CH 4 production are related to the lability of soil organic carbon compounds Bridgham and Richardson, 1992;Crozier et al, 1995), suggesting that carbon quality has a strong influence on rates of greenhouse gas production (Bridgham and Richardson, 1992;Wagner et al, 2005;Reiche et al, 2010).…”
Section: Role Of Electron Donors: Carbon Quantity and Qualitysupporting
confidence: 90%
“…For example, increased salinity caused by sea level rise may cause a change in soil carbon quality (i.e., potential for microbial mineralization) through changes in plant species composition (Gough and Grace, 1998;Baldwin et al, 2001;Donnelly and Bertness, 2001). Carbon quality contributes to differences in organic carbon mineralization by controlling the electron donor supply to decomposers (Kelley et al, 1990;Groffman et al, 1991;Schipper et al, 1994). Concomitantly, sea level rise will also influence the supply of specific TEAs, such as SO 4 2À , with uncertain effects on mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fresh pine needles supported higher denitrification rates than senescent pine needles in a riparian wetland (Schipper et al, 1994), presumably because the former had more labile compounds such as soluble carbohydrates, van Mooy et al (2002) interpreted depth-dependent changes in the ami no acid content of sinking particulate organic carbon in the Pacific Ocean as evidence that denitrifiers preferred to metabolize nitrogen-rich amino acids. If this is the case, calculations of denitrification in the eastern tropical North Pacific Ocean may be 9% higher than previous estimates that were based on typical Redfield ratios.…”
Section: Regulation Of Denitrificationmentioning
confidence: 99%
“…Other studies have found that specific types of plants, such as annuals, and specific species, such as Typha latifolia, influence denitrification enzyme activity (Crush 1998;Hernandez and Mitsch 2007;Hume et al 2002;Lin et al 2002;Patra et al 2006;Pinay et al 2007). We hypothesize that plants are likely to influence denitrification mainly via their C inputs both in terms of C quantity and quality, both of which have been shown to limit denitrification (Groffman et al 1991;Groffman and Crawford 2003;Hernandez and Mitsch 2007;Hill 1996;Hill and Cardaci 2004;Schipper et al 1994). Plants may also affect denitrification through modification of the redox conditions in the soil via root delivery of oxygen through radial oxygen loss.…”
Section: Linking Traits To Denitrification Potentialmentioning
confidence: 78%